Insertion of a miniature inverted-repeat transposable element into the promoter of OsTCP4 results in more tillers and a lower grain size in rice - Zhang, Hui (Journal of experimental botany, 2024)
© The Author(s) 2023. Published by Oxford University Press on behalf of the Society for Experimental Biology. All rights reserved. For permissions, please email: journals.permissionsoup.com.